THE INFLUENCE OF THE ROLE OF MUSDIROH AND ALL USTADZA COLLEAGUES ON ACHIEVEMENT STUDYING THE FATHUL QORIB SANTRI BOOK AT THE ISLAMIC BOARDING SCHOOL - Safitri, Sevia Diana; Masruroh, Durrotul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The achievement of studying the book Fathul Qorib for all students is crucial A solution must be found to make it easier for students to learn so they can achieve learning is in accordance with the Institution's KKM. Musdiroh or what can be called the principal if in a formal institution, along with several ustdza colleagues determines the success of students in learning to achieve students' learning achievements through the role of a leader or musdiroh who is also assisted by several ustdzah colleagues through several well-executed roles. This research was carried out in Marhalah I'dadiyah who is in Shade Ma'had Aly at the Nurul Jadid Islamic boarding school with the aim of knowing the influence of the role of Musdiroh and Ustdzah colleagues on students' book learning achievements and how big this influence is. This research using quantitative Expost Facto research with ordinal data type using Somer's D analysis. Before the data is analyzed, a test is first carried out validity and reliability of data to determine whether the data is valid or not and whether it is appropriate or not data to continue with data analysis. The results of this research have an influence between the role of musdiroh and ustdzah colleagues on learning achievement of the book of Fathul Qorib. The large influence of the role of musdiroh and ustdzah colleagues on achievement studying the book of Fathul Qorib, which is 77.9%